A Reliable Regression‐Based Approach for Reassociating Human Skeletal Elements of the Lower Limbs from Commingled Assemblages. Issue 2 (13th August 2018) - Anastopoulou, Ioanna; Karakostis, Fotios A.; Moraitis, Konstantinos
Abstract: Accurate sorting of commingled human remains comprises a fundamental requirement for all further anthropological analyses. The lower limb bones are particularly important for reconstructing biological profiles. This study introduces a metric technique for sorting these elements using eight standard anthropological measurements and 222 adult individuals from Greece. The bones utilized were the os coxae, the femora, the tibiae and the tali . Simple regression analyses were used to develop functions for reassociating articulating bones, providing strong correlations ( r  =   0.74–0.95, p ‐value <0.05) and high coefficients of determination ( r 2 =0.54–0.91). Blind tests demonstrated that combining metric and morphoscopic techniques provides an excellent sorting accuracy for the hip and knee joints (ten of ten individuals), allowing for a reliable reassociation between a sex and age indicator ( os coxae ) and a body size indicator ( femur ). Overall, these results indicate the high value of metric methods in sorting commingled human remains.